Agreement between EMS provider-assigned prehospital triage and initial emergency department triage in pediatric and adult EMS-transported encounters: A retrospective observational study - Min-Jung Kim; Hwan Sun Moon; So-Hyun Paek (PLoS ONE, 2026)
Background Prehospital triage supports destination decisions, resource activation, and early risk stratification, yet accurate triage of children in the field remains challenging. In South Korea, a five-level emergency department triage framework has recently been extended to the Prehospital setting through nationwide implementation of a prehospital triage scale. This study aimed to evaluate agreement between EMS provider-assigned prehospital triage and initial ED triage, with a pediatric-focused primary analysis and adults as a secondary comparator. Methods We conducted a retrospective observational study using linked EMS run-sheet and emergency department records from one university hospital during the first year of nationwide implementation (February–December 2024). We included all EMS-transported emergency department encounters that were registered and assigned an initial emergency department triage level on arrival. Agreement between prehospital and emergency department triage levels was assessed using overall exact agreement, Cohen’s unweighted κ, and quadratically weighted κ. Results Among 5,182 EMS-transported emergency department encounters during the study period, 4,729 were included in the final analysis, comprising 1,242 pediatric and 3,487 adult encounters. Overall agreement was 47.7% in pediatric encounters and 52.8% in adults. Quadratically weighted κ indicated modest agreement in children (0.27) and higher agreement in adult encounters (0.40). Disagreement was concentrated at adjacent-level boundaries, particularly between levels 2–3 and 3–4. Discordance toward higher prehospital acuity predominated in pediatric encounters, whereas discordance toward lower prehospital acuity was more common in adults. Conclusions During the first year of nationwide implementation, prehospital and emergency department triage showed modest agreement, with lower concordance and a predominance of discordance toward higher prehospital acuity in pediatric encounters. Adjacent-level boundaries represent practical targets for pediatric-focused training and feedback to improve consistency of prehospital triage assignments.